Detection and Seismic Study of Gravity and Rossby Mode Pulsations in Four Contact Binaries - X. B. Zhang; Xinghao Chen; Jianning Fu; Yan Li (The Astrophysical Journal, 2023)
We report the detection of gravity ( g ) and Rossby ( r ) mode pulsations of four short-period eclipsing binaries, KIC 5439790, KIC 7501230, KIC 9350889, and KIC 9453192 based on the 4 yr Kepler high-precision photometry. Light-curve modeling reveals that the four binaries are all contact systems with small mass ratios. We study the short-term variability of the light-curve residuals after the removal of the binary model and attribute them to the g- and r -mode pulsations that stem from the primary stars. By introducing a new criterion, we attempt to identify period-spacing patterns in the Fourier spectra, which refers to the determination of the rotation rates of stellar interior and envelope as well as the asymptotic period spacings of the pulsating stars. It is interesting to find that the rotation rates of the stellar envelopes are all nearly equal to the orbits. The near-core rotations, however, are significantly slower by about 10%. Based on the derived asymptotic period spacings, stellar parameters were constrained from asteroseismology models. The pulsators are revealed to be evolved main-sequence stars with high metallicities.